Occurrence, identification and transmission of the phytoplasma associated with tomato big bud disease and identification of its vector and weed host in Pakistan. (9th May 2018) - Akhtar, Khalid Pervaiz; Saleem, Muhammad Yussouf; Yousaf, Sumaira; Ullah, Najeeb; Rasool, Ghulam; Sarwar, Nighat
Abstract: Tomato ( Solanum lycopersicum L.) plants showing stunting, big bud, leaves yellowing or reddening and witches'-broom symptoms were observed since 2009 in Pakistan. A weed Parthenium hysterophorus grown in and around tomato fields also exhibited witches'-broom like symptoms. Fluorescence light microscopy of hand-cut stem stalk sections treated with Dienes' stain showed blue areas in the phloem region of both tomato and P. hysterophorus symptomatic plants that indicated the association of phytoplasma with the complex. Amplification of 1.2 kb 16S rDNA fragment in nested PCR confirmed that the symptomatic tomato and P. hysterophorus plants are infected by a phytoplasma. Partial sequencing of 16S rRNA (GenBank accession: LT671581 and LT671583) and virtual restriction fragment length polymorphism confirmed that the phytoplasma associated with both plant species had the greatest homology to 16SrII-D subgroup. Disease was successfully transmitted by grafting and leafhopper Orosius albicinctus in tomato plants. This is the first report of natural occurrence of 16SrII-D phytoplasma in tomatoes and a weed P. hysterophorus in Pakistan.